One-step and low-temperature synthesis of monetite nanoparticles in an all-in-one system (reactant, solvent, and template) based on calcium chloride-choline chloride deep eutectic medium. Issue 2 (1st February 2017) - Karimi, Mohammad; Rastegar Ramsheh, Majid; Mohammad Ahmadi, Seyed; Reza Madani, Mohammad
Abstract: Monetite nanoparticles were synthesized via a facile and sustainable method using deep eutectic medium based on CaCl2 ·6H2 O-choline chloride to act as solvent, reactant and template. The synthesized nanoparticles were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), and Fourier transform infrared spectroscopy (FTIR). Analysis data revealed the formation of CaHPO4 nanoparticles crystalized in anorthic structure with spherical morphology, mean particle size of 65 nm, and high elemental-structural purity. The results suggested the ternary role of the eutectic system in synthesis of monetite nanoparticles providing the synthesis medium, calcium-active reaction sites, and electrosteric stabilization by which the deep eutectic system can control the particle growth and agglomeration of monetite.